Anomalous mechanical materials squeezing three-dimensional volume compressibility into one dimension - Xingxing Jiang (Nature Portfolio, 2020)
Anomalous mechanical behaviors provide an opportunity to regulate the functions of materials. Here the authors show that materials with coexisting negative, zero and positive compressibilities can “squeeze” volume compressibility into one direction, and thus stabilize transmission processes under pressure.